1990
DOI: 10.1007/bf00196228
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic functions of tandem repeated DNA sequence blocks in the human genome are based on a highly conserved ?chromatin folding code?

Abstract: This review is based on a thorough description of the structure and sequence organization of tandemly organized repetitive DNA sequence families in the human genome; it is aimed at revealing the locus-specific sequence organization of tandemly repetitive sequence structures as a highly conserved DNA sequence code. These repetitive so-called "super-structures" or "higher-order" structures are able to attract specific nuclear proteins. I shall define this code therefore as a "chromatin folding code". Since locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 300 publications
(280 reference statements)
2
122
0
1
Order By: Relevance
“…33,34 Whether these transcripts affect the chromatin structure, which in turn modifies the transcriptional activity of DGS/VCFS genes, remains to be determined. 35 An alternative possibility is that the DGS/CVFS phenotype results from alteration of the 'chromatin folding code' mediated by the deletion of low-copy DNA repeats within 36 Interestingly, a recent report has shown that chromosome breakpoints in DGS/VCFS patients occur within low-copy DNA repeats (LCR22s), 37 which overlap the five intervals described here. Another contribution to the understanding of DGS/VCFS molecular pathogenesis could be the engineering of mice carrying deletions mimicking the five DGS/VCFS intervals.…”
Section: Resultsmentioning
confidence: 77%
“…33,34 Whether these transcripts affect the chromatin structure, which in turn modifies the transcriptional activity of DGS/VCFS genes, remains to be determined. 35 An alternative possibility is that the DGS/CVFS phenotype results from alteration of the 'chromatin folding code' mediated by the deletion of low-copy DNA repeats within 36 Interestingly, a recent report has shown that chromosome breakpoints in DGS/VCFS patients occur within low-copy DNA repeats (LCR22s), 37 which overlap the five intervals described here. Another contribution to the understanding of DGS/VCFS molecular pathogenesis could be the engineering of mice carrying deletions mimicking the five DGS/VCFS intervals.…”
Section: Resultsmentioning
confidence: 77%
“…2), which has a high potential to form the Z-DNA structure (23,24). The structural transition from a righthanded B-DNA conformation to a left-handed Z-DNA conformation has been shown to regulate gene transcription (25,26). It should also be noted that SNPs altering gene expression and those associated with diseases are often found in the CA repeat sequences (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite sequences of 1-5 nucleotides per unit repeat are found throughout the human genome [1][2][3][4][5][6][7][8]. Microsatellite sequences are often hotspots for mutation, and an increase in mutagenesis is observed as the length of the repeated sequence increases [9,10].…”
Section: Introductionmentioning
confidence: 99%